Arthroscopic Technique to Reduce Suture Button Migration During Anterior Cruciate Ligament Reconstruction Procedure - Ohnishi, Yasuo (Arthrosc Tech, 2017)
Suture button–based femoral cortical suspension constructs of anterior cruciate ligament grafts can facilitate a fast and secure fixation. However, there are several case reports showing button malpositioning resulting from the inability to visualize the “flipped” button. Many current surgical techniques do not allow direct visualization of EndoButtons (Smith & Nephew, Andover, MA) in their final position, making it difficult to ensure that both buttons are fully flipped and that there is no soft-tissue interposition between the button and femur. We describe an arthroscopic technique for making femoral tunnels through the outside-in method that reduces the migration of the EndoButton through a lateral femoral portal. This technique may assist surgeons in understanding how to deal with and potentially avoid EndoButton migration during anterior cruciate ligament reconstruction.